The effect of age and sex on serum proteins in the Pega donkey (Equus asinus) - Girardi, A. M. [UNESP]; Toledo, C. Z. P. [UNESP]; Silva, P. C. [UNESP]; Marques, L. C. [UNESP] (Czech Academy Agricultural Sciences, 2017)
In this study sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) was used to evaluate the influence of age and sex on serum proteins in 110 Pega donkeys, 79 females and 31 males, classified into three age groups (under one year - eight animals; one to three years - 33 animals and over three years old - 69 animals). SDS-PAGE allowed identification of 10 serum proteins, some with unknown functions. No age-related differences were observed (P > 0.05) for haptoglobin, alpha(1)-acid glycoprotein and 23 kDa molecular weight protein (MWP23) and no sex-related differences (P > 0.05) for immunoglobulin A, albumin, MWP23 and haptoglobin. With advancing age, immunoglobulin A levels decreased (P < 0.001), whereas immunoglobulin G levels increased (P < 0.001). The youngest donkeys showed the lowest albumin (P < 0.001) and 33 kDa molecular weight protein (MWP33) (P < 0.05) means. The oldest group showed a higher transferrin mean (P < 0.05) than the youngest one. Animals between one and three years had the highest mean (P < 0.001) for 138 kDa molecular weight protein (MWP138). Animals over three years showed higher ceruloplasmin levels (P < 0.05) than the one-to-three year old group. Males showed greater means of MWP138 (P < 0.05), ceruloplasmin (P < 0.05), alpha(1)-acid glycoprotein (P < 0.001) and MWP33 (P < 0.01). Females had higher transferrin (P < 0.001) and immunoglobulin G (P < 0.001) concentrations. Sex and age influenced the levels of the majority of proteins in the serum profile of Pega donkeys, including some acute phase proteins. Our results differ from those of previous studies in the effects of breed and environmental factors on some of the measured variables.
Keywords: acute-phase proteins; biochemistry; blood protein electrophoresis; SDS-PAGE